13th International Behavioral Ecology Conferences - Barata, Eduardo N. (2010)
Temperament is usually described as a continuum, with "bold" and "shy" ends. As the former are described as more active and more prone to take risks, they are expected to have higher metabolic requirements and thus higher ventilatory rates, compared to the opposite extreme of "shy" temperament. In this study we aimed at determining the temperament types of a Mozambique tilapia (Oreochromis mossambicus) male population in the "shyness-boldness" continuum and its possible relation with the opercular ventilatory frequency. We used a noninvasive method to quantify these frequencies and the new object’s paradigm to determine the temperament of the subjects. We found a significant relation between temperament and opercular ventilatory frequency in O. mossambicus males. Males with "bold" temperament showed significantly higher ventilation rates than "shy" males, which expressed the lower ventilation rates. Males with "intermediate" temperament expressed frequencies between the two extremes of the continuum. Also, and as predicted, temperament had an influence on these individuals’ activity and exploratory behaviour: “bold” and “intermediate” males were simultaneously more active and showed a significantly higher exploratory behaviour than "shy" males. Our results also suggest that selection in captivity can act in order to favor "bold" individuals.